2003
DOI: 10.1113/jphysiol.2003.040303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C Supplements on Antioxidant Defence and Stress Proteins in Human Lymphocytes and Skeletal Muscle

Abstract: Oxidative stress induces adaptations in the expression of protective enzymes and heat shock proteins (HSPs) in a variety of tissues. We have examined the possibility that supplementation of subjects with the nutritional antioxidant, vitamin C, influences the ability of lymphocytes to express protective enzymes and HSPs following exposure to an exogenous oxidant and the response of skeletal muscle to the physiological oxidative stress that occurs during exercise in vivo. Our hypothesis was that an elevation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
178
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(199 citation statements)
references
References 37 publications
16
178
3
2
Order By: Relevance
“…Our modest changes in antioxidant system agrees with the results obtained in previous studies after static and dynamic apnoeas (Joulia et al, 2002;Joulia et al, 2003). Increased ROS production can activate the CAT in erythrocytes (Tauler et al, 1999) and induce the synthesis of antioxidant enzymes such as SOD in lymphocytes (Khassaf et al, 2003;Tauler et al, 2003). We previously reported that exhaustive exercise induced a general increase in the lymphocyte antioxidant enzyme activities, which could be influenced by vitamin C supplementation (Tauler et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Our modest changes in antioxidant system agrees with the results obtained in previous studies after static and dynamic apnoeas (Joulia et al, 2002;Joulia et al, 2003). Increased ROS production can activate the CAT in erythrocytes (Tauler et al, 1999) and induce the synthesis of antioxidant enzymes such as SOD in lymphocytes (Khassaf et al, 2003;Tauler et al, 2003). We previously reported that exhaustive exercise induced a general increase in the lymphocyte antioxidant enzyme activities, which could be influenced by vitamin C supplementation (Tauler et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…29 the oxidative stress in leucocytes induced by hypertension could provoke, as observed in our results, an increase and not a decrease in SOD and CAT activities. Treatment with eprosartan leads to a reduction in these activities, parallel to the normalisation of blood pressure values.…”
Section: Figuresupporting
confidence: 52%
“…A single period of contractile activity in mouse muscle was found to increase muscle SOD and catalase activity together with HSP60 and HSP70 content , changes which were replicated in human muscle (Khassaf et al 2001). Pre-supplementation with vitamin C reduced these responses, supporting the possibility that they are regulated by ROS (Khassaf et al 2003). The possibility that ROS can directly modulate stress responses to contraction in skeletal muscle has been examined by using Clontech cDNA expression arrays to determine whether hydrogen peroxide treatment could induce changes in stress gene expression in skeletal muscle in culture and comparison of these changes with those seen in skeletal muscle in vivo at the same time points following a period of non-damaging contractile activity known to induce a substantial generation of oxidants .…”
Section: Functions Of Ros In Skeletal Musclementioning
confidence: 64%